Low or undetectable TPO receptor expression in malignant tissue and cell lines derived from breast, lung, and ovarian tumors - Erickson-Miller, Connie L (BioMed Central, 2012)
BACKGROUND: Numerous efficacious chemotherapy regimens may cause thrombocytopenia. Thrombopoietin receptor (TPO-R) agonists, such as eltrombopag, represent a novel approach for the treatment of chemotherapy-induced thrombocytopenia. The TPO-R MPL is expressed on megakaryocytes and megakaryocyte precursors, although little is known about its expression on other tissues. METHODS: Breast, lung, and ovarian tumor samples were analyzed for MPL expression by microarray and/or quantitative reverse transcription-polymerase chain reaction (qRT-PCR), and for TPO-R protein expression by immunohistochemistry (IHC). Cell line proliferation assays were used to analyze the in vitro effect of eltrombopag on breast, lung, and ovarian tumor cell proliferation. The lung carcinoma cell lines were also analyzed for TPO-R protein expression by Western blot. RESULTS: MPL mRNA was not detectable in 118 breast tumors and was detectable at only very low levels in 48% of 29 lung tumors studied by microarray analysis. By qRT-PCR, low but detectable levels of MPL mRNA were detectable in some normal (14-43%) and malignant (3-17%) breast, lung, and ovarian tissues. A comparison of MPL to EPOR, ERBB2, and IGF1R mRNA demonstrates that MPL mRNA levels were far lower than those of EPOR and ERBB2 mRNA in the same tissues. IHC analysis showed negligible TPO-R protein expression in tumor tissues, confirming mRNA analysis. Culture of breast, lung, and ovarian carcinoma cell lines showed no increase, and in fact, showed a decrease in proliferation following incubation with eltrombopag. Western blot analyses revealed no detectable TPO-R protein expression in the lung carcinoma cell lines. CONCLUSIONS: Multiple analyses of breast, lung, and ovarian tumor samples and/or cell lines show no evidence of MPL mRNA or TPO-R protein expression. Eltrombopag does not stimulate growth of breast, lung, or ovarian tumor cell lines at doses likely to exert their actions on megakaryocytes and megakaryocyte precursors.